Assumptions create exposure to claims of transgender discrimination. Issue 9 (November 2015) - Porter, Michael
<x xml:space="preserve">Abstract</x> Although some higher ed administrators have a firm grasp on the legal aspects of providing adequate support and access to transgender students, staff and faculty members, many other administrators may be at a loss, leaving their institutions exposed to legal risk.